Evaluation of the effect of 48 weeks of BIC/F/TAF and DRV/c/F/TAF on platelet function in the context of rapid ART start - Akif A. Khawaja; Gary Whitlock; Sarah Fidler; Alfredo Soler-Carracedo; Merle Henderson; Graham P. Taylor; Marta Boffito; Michael Emerson (HIV Research & Clinical Practice)
Introduction The BIC-T&T study aimed to determine the efficacy of bictegravir/emtricitabine/tenofovir alafenamide (BIC/F/TAF) and darunavir/cobicistat/emtricitabine/tenofovir alafenamide (DRV/c/F/TAF) at suppressing viral load in a two-arm, open-label, multi-centre, randomised trial under a UK test-and-treat setting. This sub-study aimed to evaluate potential off-target cardiovascular impact by examining ex vivo platelet function. Methods Platelets were isolated by centrifugation of citrated blood from participants attending Chelsea and Westminster Hospital or St Mary’s Hospital at Week 48 following enrolment. Platelet activation was assessed by real-time flow cytometry to examine integrin activation and granule release and platelet aggregation was evaluated by light transmission aggregometry. Statistical significance was determined by 2-way ANOVA with a Šidák’s multiple comparisons post-test. Results An analysis of 21 participants was performed at Week 48 (96% male and 48% white; mean (range) age was 37 (23–78) years). No difference between arms was observed in ADP-, collagen- or thrombin receptor activator for peptide (TRAP)-6-evoked platelet αIIbβ3 integrin activation, granule release or platelet aggregation in response to any of the agonists tested. Despite differences in the demographics between treatment arms, the presence of an unboosted integrase inhibitor or boosted protease inhibitor in a test-and-treat setting did not impact platelet function. Conclusions Our study provides no evidence of differences in downstream platelet responses between participants taking BIC/F/TAF compared to DRV/c/F/TAF following 48 wk of treatment. Further data are required to explore whether there are biologically significant off-target effects, including effects on platelets and other components of the cardiovascular system between these two test-and-treat regimens. Clinical Trial Number NCT04653194.